1986
DOI: 10.1017/s0022172400066365
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus type 8 keratoconjunctivitis – an outbreak and its treatment with topical human fibroblast interferon

Abstract: An outbreak of keratoconjunctivitis is described which involved at least 186 people; adenovirus type 8 was identified in 50 of the cases. Topical human fibroblast interferon was assessed in a double-blind, placebo-controlled study in which 34 patients participated. Seventeen of the 34 trial patients yielded adenovirus type 8; three were infected with adenovirus type 7. The outbreak was curtailed by control of infection measures: principally careful hand-washing by medical personnel between cases and by discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…The duration of the disease observed in this outbreak was basically consistent with that of a previous study [36]. Regarding the risk factors for transmission, previous studies have focused on risk factors for transmission in hospitals [25,27,[31][32][33][34][35][36][37]. Our research reveals the risk factors for school transmission in remote areas in developing countries.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The duration of the disease observed in this outbreak was basically consistent with that of a previous study [36]. Regarding the risk factors for transmission, previous studies have focused on risk factors for transmission in hospitals [25,27,[31][32][33][34][35][36][37]. Our research reveals the risk factors for school transmission in remote areas in developing countries.…”
Section: Discussionsupporting
confidence: 88%
“…Since the 1980s, EKC outbreaks caused by HAdV-8 have been reported in different countries and regions of the world. Most of the outbreaks were caused by iatrogenic ophthalmic transmission in hospitals [25,27,[31][32][33][34][35][36][37]. Two outbreaks of EKC in two schools in the Tibet autonomous region were reported for the first time in mainland China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, purine and pyrimidine base analogs, such as ganciclovir, have been studied as both topical and internal medications and may show some promise (9,11,23,24,41,78,94,116,128,131,138). Otherwise, the best strategies are those of prevention, which have been successfully applied to curtail adenovirus outbreaks in ophthalmologic clinics, hospitals, and nurseries (15,96,129).…”
Section: Adenoviruses In Primary Immunodeficienciesmentioning
confidence: 99%
“…reported that topical IFN‐β was effective against an AdV8‐induced nosocomial outbreak of keratoconjunctivitis 19 . However, although a placebo‐controlled trial was carried out in that study, no statistically significant difference was observed in the recovery rate of patients receiving IFN‐β or placebo, possibly because of the small scale of the study 19 . In contrast, six times daily application of 2–5 × 10 5 IU IFN‐β eye drops reduced the duration of disease and prevented corneal subepithelial opacity in 45% of cases 15 .…”
Section: Discussionmentioning
confidence: 99%